Analisis Kualitas Website PSSI Jawa Tengah Menggunakan Metode WebQual 4.0 - Nayaka Jati Riyono; Jazimatul Husna (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This study aims to evaluate the quality of the Central Java PSSI website based on user perceptions using the WebQual 4.0 method. The Central Java PSSI website functions as the organization’s official information media for delivering news, competition information, and regional football-related services to the public. However, several limitations were identified in terms of design, content consistency, and service interaction, which may affect user experience. This research employed a quantitative approach with a survey method. Data were collected through an online questionnaire distributed to users who had previously accessed and used the Central Java PSSI website. The research instrument was developed based on the three dimensions of WebQual 4.0, namely usability quality, information quality, and service interaction quality. A total of 123 respondents participated in this study and were selected using purposive sampling techniques. The data were analyzed descriptively using IBM SPSS Statistics 26 by calculating the mean score of each indicator. The results indicate that the overall quality of the Central Java PSSI website is categorized as good. The usability quality dimension shows that the website is easy to use and understand, although the visual design is considered relatively monotonous. The information quality dimension indicates that the information provided is sufficiently complete, relevant, and understandable, despite several pages not being managed optimally. The service interaction quality dimension demonstrates a high level of user trust toward the website; however, direct communication aspects through contact information still need improvement. Based on the findings, improvements in design, content consistency, and communication accessibility are necessary to optimize website quality further.